What Evidence Exists on Individuals' Sustainable Consumption Practices in Africa? A Scoping Review Protocol - Ansu-Mensah, Peter; Ansu-Mensah, Monica; Kuupiel, Desmond (International Review of Management and Marketing, 2021)
The new paradigm shift in the discourse on sustainability and sustainable consumption globally and particularly in Africa, has led to the need to understand the consumption practices of people in order to strategize and safeguard scarce natural resources for posterity. This study aims to systematically review published research to answer the research question: what evidence exists on individuals' sustainable consumption practices in Africa? The study focuses on consumers' waste minimisation, sustainable food consumption, sustainable transport and sustainable energy consumption in Africa, to provide evidence for policy decisions and future research. The study adopts the 2015 Joanna Briggs Institute guidelines, Arksey and O'Malley's suggested scoping review framework, and Levac et al. 2010 recommendations. To present the results of this review, the Preferred Reporting Items for Systematic Reviews and Meta-analysis Extension for Scoping Review would be used. This study seeks to identify future strategies to encourage greater sustainable consumption practices in African households. Keywords: Sustainable consumption and production, Waste minimisation, Sustainable food consumption, Sustainable energy consumption, Sustainable transport, Africa JEL Classifications: M31, P28, P36, Q01, Q56 DOI: https://doi.org/10.32479/irmm.11845